COMMERCIAL LIFE POPULATION-DEMAND RELATIONSHIP AND PEOPLE LIVINGLIFE IN BYZANTINE EMPIRE (VII-X. CENTURIES) - BAMYACI, Mehmet Ertan (SSD Journal, 2018)
Commerce took an important place in the life of the Byzantine Empireand the fact that the capital Constantinople was a huge trading center was the most important proof of this. In the Byzantine capital, the commercial activities were highly intensive and one of the most important reasons of this intensity in trade is undoubtedly because Constantinople was a crowded city. The dense population in the city was fueling the commercial intensity, and the commercial intensity was setting the stage for the population increase again. By the time we had examined, Constantinople had a relatively large population compared to other medieval cities. It was thought that there was a population of around 10 million in the end of the Xth centurythroughout the empire,it can be estimated that how large the commercial potential of Byzantiumwas. In the economic life of the empire, it is clear that commercewas directly connected to population.In this direction, it is a fact that the intensity of commerce in the cities will be different from the concentration of commerce in the countryside. In Byzantine cities, commercial activities were livelier than countryside areas. Consumption in rural areas was mostly based on products that people produced with their own means. The people living in the countryside were able to produce almost all of the products that could resign their lives with their own meansand this people's way of life was shaped by the land that played a leading role in their lives.In the life of this people who live on the land, agriculture and animal husbandry werethe basic occupation. Every household could supply almost all their basic needs with these sectors they were dealing with. At this point, the people of the countryside constituted the production dimension of commerce. The public marketed the increasing share of their needs and taxes by taking them to densely populated areas and cities that were close to them. Production was also taking place in the cities, but the consumption was considerably higher depending on the population density. At this point, the people of the city constituted the dimension of consumption of commerce in terms of density. Unlike countryside life, there was also a big gap between the rich and the poor in the cities.In this case, we can also say that the demand for commercial products in cities differs according to the rich and the poor. In the Empire, a wealthy city man had the opportunity to give a monthly income of a poor countryside man, to an ornamental material by unseen way.